2022
DOI: 10.3390/ijms23094992
|View full text |Cite
|
Sign up to set email alerts
|

Low Concentration of the Neutrophil Proteases Cathepsin G, Cathepsin B, Proteinase-3 and Metalloproteinase-9 Induce Biofilm Formation in Non-Biofilm-Forming Staphylococcus epidermidis Isolates

Abstract: Neutrophils play a crucial role in eliminating bacteria that invade the human body; however, cathepsin G can induce biofilm formation in a non-biofilm-forming Staphylococcus epidermidis 1457 strain, suggesting that neutrophil proteases may be involved in biofilm formation. Cathepsin G, cathepsin B, proteinase-3, and metalloproteinase-9 (MMP-9) from neutrophils were tested on the biofilm induction in commensal (skin isolated) and clinical non-biofilm-forming S. epidermidis isolates. From 81 isolates, 53 (74%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In addition, another study showed that cathepsin G, cathepsin B, metalloproteinase 9, and neutrophil proteinase 3 induce biofilm formation in S. epidermidis isolates with a non-biofilm-producing phenotype. It was also shown that S. epidermidis with a non-biofilmproducing phenotype in the presence of neutrophil, the biofilm is induced by the release of the proteases mentioned above (Gómez-Alonso et al, 2022). These observations strongly suggest that S. epidermidis has taken advantage of releasing neutrophil granule contents as neutrophil proteases cleave Aap protein for biofilm formation.…”
Section: Evasion Of the Neutrophil Response By S Epidermidis Biofilmmentioning
confidence: 80%
“…In addition, another study showed that cathepsin G, cathepsin B, metalloproteinase 9, and neutrophil proteinase 3 induce biofilm formation in S. epidermidis isolates with a non-biofilm-producing phenotype. It was also shown that S. epidermidis with a non-biofilmproducing phenotype in the presence of neutrophil, the biofilm is induced by the release of the proteases mentioned above (Gómez-Alonso et al, 2022). These observations strongly suggest that S. epidermidis has taken advantage of releasing neutrophil granule contents as neutrophil proteases cleave Aap protein for biofilm formation.…”
Section: Evasion Of the Neutrophil Response By S Epidermidis Biofilmmentioning
confidence: 80%
“…We have reported that S. epidermidis isolates from PJI are more resistant to biofilm production under various in vitro biofilm induction conditions and that most commensal isolates do not form biofilms 42 . Furthermore, commensal isolates from healthy skin can induce biofilm formation when exposed to neutrophil proteases, such as cathepsin G, cathepsin B, proteinase-3 and metalloproteinase-9 53 . In this study, we demonstrated that both the clinical isolate Se353 and commensal isolate HS145 affected osteoblast function, suggesting that their influence on osteoblast function is independent of biofilm status, which is surprising because it is well known that commensal isolates are not potentially virulent.…”
Section: Discussionmentioning
confidence: 99%
“…Both genes are required for Aap-dependent S. epidermidis biofilm formation. Indeed, in a recent paper [83], Gomez-Alonso et al demonstrated the induction of biofilm production by neutrophil proteases in non-biofilm-forming commensal isolates of S. epidermidis. More precisely, commensal isolates with icaA−, icaD− and aap+, sepA+ genotypes, which had previously been recognized as non-biofilm-forming, produced biofilms in the presence of neutrophilic proteases such as cathepsin G, cathepsin B, proteinase-3 and MM-9 in neutrophils.…”
Section: Biofilm Proteinsmentioning
confidence: 99%
“…More precisely, commensal isolates with icaA−, icaD− and aap+, sepA+ genotypes, which had previously been recognized as non-biofilm-forming, produced biofilms in the presence of neutrophilic proteases such as cathepsin G, cathepsin B, proteinase-3 and MM-9 in neutrophils. Neutrophils do not generate NETs against commensal bacteria but produce proteases that help commensal bacteria in survival [83]. Aap contributes both to the initial attachment phase and to the intercellular connections, with each cell stretching twisted fibrils of truncated Aap to interact with the neighboring cells.…”
Section: Biofilm Proteinsmentioning
confidence: 99%